Effects of financial literacy on graduate school attitudes amidst COVID‐19. (1st December 2021) - Chan, Kam C.; Chang, Samuel; Snavely, Jean C.
Abstract : This study examines the relationship between financial literacy and student attitudes toward graduate school. In the framework of human capital theory, we argue that graduate school is an investment in an individual's human capital that enhances future earnings capability. We hypothesize that during a weakened job market in conjunction with the COVID‐19 pandemic that students who are more financially literate will demonstrate a more positive attitude toward a graduate degree as an appealing and rewarding capital investment than students with less financial literacy. Our robust results are consistent with our hypothesis. We argue that these findings have significant economic implications.